2022
DOI: 10.1021/acs.jpcc.2c04863
|View full text |Cite
|
Sign up to set email alerts
|

Low Threshold, High Q-Factor Optically Pumped Organic Lasers and Exciton Dynamics in OLEDs under High Current Density: Singlet–Triplet Annihilation Effect and toward Electrical Injection Lasing

Abstract: The realization of electrically pumped organic semiconductor lasers needs to suppress singlet–triplet annihilation (STA) as much as possible. Generally, organic gain medium materials suffer extensive loss of singlet excitons through STA, resulting in extremely high lasing threshold current density (J th) on the order of 10–100 kA cm–2. Herein, we study the lasing and electroluminescence (EL) properties of a new organic gain material, named PIO, with low STA. As shown, it exhibits remarkable optical gain and EL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The high radiative rate represents the large, stimulated emission cross section. A formula is used to estimate the stimulated emission cross section (𝜎 SE (𝜆)), as shown below: [19] 𝜎…”
Section: Photophysical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The high radiative rate represents the large, stimulated emission cross section. A formula is used to estimate the stimulated emission cross section (𝜎 SE (𝜆)), as shown below: [19] 𝜎…”
Section: Photophysical Propertiesmentioning
confidence: 99%
“…Based on the good basic photophysical results, the gain properties of PIO, PIPhDPO, and PI2PhDPO were studied by ASE measurements. Because of the high Förster energy transfer rate between mCP and PPI derivatives, [19] we prepared the doped thin films by doping PIO, PIPhDPO, and PI2PhDPO in mCP with a concentration of 8% by spin-coated method. The thin films were produced on preclean silica substrates and the thickness is in the region of 140-160 nm.…”
Section: Ase Properties Under Low Pump Repetition Frequencymentioning
confidence: 99%
See 1 more Smart Citation
“…6–8 Great effort has been expended to solve the previous issues. 8–12 Recently, Nakanotani et al . first observed the amplified spontaneous emission (ASE) in a thermally activated delayed fluorescence (TADF) material, DABNA-2.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Great effort has been expended to solve the previous issues. [8][9][10][11][12] Recently, Nakanotani et al first observed the amplified spontaneous emission (ASE) in a thermally activated delayed fluorescence (TADF) material, DABNA-2. Thus, the study of TADF gain media has become a research hotspot because the reverse intersystem crossing (RISC) process can utilize triplet excitons, and in turn suppress the 'pile-up' effect from triplet excitons.…”
Section: Introductionmentioning
confidence: 99%